Introducing a new open source GIS user interface for the SWAT model. (November 2016) - Dile, Yihun T.; Daggupati, Prasad; George, Chris; Srinivasan, Raghavan; Arnold, Jeff
Abstract: The Soil and Water Assessment Tool (SWAT) model is a robust watershed modeling tool. It typically uses the ArcSWAT interface to create its inputs. ArcSWAT is public domain software which works in the licensed ArcGIS environment. The aim of this paper was to develop an open source user interface for the SWAT model. The interface, QSWAT, is written in the Python programming language and uses various functionalities of the open source geographic information system, QGIS. The current interface performs similar functions to ArcSWAT, but with additional enhanced features such as merging small subbasins and static and dynamic visualization of outputs. The interface is demonstrated through a case study in the Gumera watershed in the Lake Tana basin of Ethiopia, where it showed a successful performance. QSWAT will be a valuable tool for the SWAT scientific community, with improved availability and functionality compared with other options for creating SWAT models. Highlights: Open source software called QSWAT was developed on the QGIS platform. The software creates input data and executes the SWAT model. It can provide static and dynamic visualization of outputs. A case study utilizing the software demonstrated a very good performance. The tool is beneficial to users in developing countries.